Investigating the human spirit and spirituality in pediatric patients with kidney disease - Woroniecki, Robert; Moritz, Michael L. (Frontiers in Pediatrics, 2023)
Human spirit is an integral part of the medicinal art and science trifecta: body-mind-spirit, and it is contained in the World Health Organization definition of health. Human spirit is defined as our purpose in life, relationships with all living creatures or “Higher Power”, and in general our place on planet Earth. Spirituality is a required part of patient care according to Joint Commission on Accreditation of Health Care Organizations. There is an abundant medical literature that documents discrepancies in the results between studies and populations, and points to the importance of cultural, ethnic, spiritual or religious differences. Validated questionnaires used in research for last several decades demonstrated an association of spirituality with clinical outcomes, coping, and quality of life in different adult chronic diseases. There are also validated scales to measure hope in children based on the premise that children are goal directed and that their goal-related thoughts can be understood, yet their purposefulness, meaning of life and spirit in pediatric nephrology remains mostly unexamined. Although pediatric nephrology has made significant advances in molecular techniques, artificial intelligence, machine learning, and started to address more broad social issues such as racism, health equity, diversity of our work force, etc, it lacks both systematic ways of studying and philosophical approach to fostering human spirit. This mini review examines the place and knowledge gaps in human spirit and spirituality in pediatric nephrology. We review the concept of the human spirit and medical literature pertaining to its role in pediatric nephrology.